Influence of patient characteristics and immunosuppressant management on mortality in kidney transplant recipients hospitalized with coronavirus disease 2019 (COVID‐19). Issue 4 (21st January 2021) - Santeusanio, Andrew D.; Menon, Madhav C.; Liu, Caroline; Bhansali, Arjun; Patel, Niralee; Mahir, Fahima; Rana, Meenakshi; Tedla, Fasika; Mahamid, Ahmad; Fenig, Yaniv; Zendel, Alexey; Delaney, Veronica; et al.
Abstract: The influence of patient characteristics and immunosuppression management on COVID‐19 outcomes in kidney transplant recipients (KTRs) remains uncertain. We performed a single‐center, retrospective review of all adult KTRs admitted to the hospital with confirmed COVID‐19 between 03/15/2020 and 05/15/2020. Patients were followed from the date of admission up to 1 month following hospital discharge or study conclusion (06/15/2020). Baseline characteristics, laboratory parameters, and immunosuppression were compared between survivors and patients who died to identify predictors of mortality. 38 KTRs with a mean baseline eGFR of 52.5 ml/min/1.73 m 2 were hospitalized during the review period. Maintenance immunosuppression included tacrolimus (84.2%), mycophenolate (89.5%), and corticosteroids (81.6%) in the majority of patients. Eleven patients (28.9%) died during the hospitalization. Older age (OR = 2.05; 1.04‐4.04), peak D‐dimer (OR = 1.20; 1.04‐1.39), and peak white blood cell count (OR = 1.11; 1.02‐1.21) were all associated with mortality among KTRs hospitalized for COVID‐19. Increased mortality was also observed among KTRs with concomitant HIV infection (87.5% vs. 36.1%; p < .01). Conversely, immunosuppression intensity and degree of reduction following COVID‐19 diagnosis were not associated with either survival or acute allograft rejection. Our findings potentially support a strategy of individualization of immunosuppression targets based on patient‐specific risk factors, rather than universal immunosuppression reduction for KTRs at risk from COVID‐19.